Quick Homework Help

# How  do you  solve The sum of three consecutive integers is -66 Find the integers ⚑ Flag

by Melanie131 at June 01, 2011

Set up an equation:x + (x+1) + (x+2) = -66x is your first number, (x+1) is the number after, etc.Combine like terms:3x + 3 = -66Then solve:3x + 3 = -663x = -69x = -23So, plugging x back into the equation...(-23) + (-23 + 1) + (-23 + 2) = -66-23 + -22 + -21 = -66-66 = -66The answer is -23, -22, and -21.

JoshuaThomas June 01, 2011

Hi Melenie131,           To solve this problem, we need to set up an equation. First, we set our our equals value ( in this case the sum of the integers which is -66)  Now, we can set some variables. We can use the information givin to do this.We know there are three consecutive intergers adding up to -66. (These intergers are most likley negative). Lets call the first of the three intergers X. We proceed  by adding the second interger, which we can label X-1. (This occurs by use of the rule of signs, if I had -1 and added -1 to it, the sum would be -2 I can keep going consecutivly in this manner) By this logic, we add the third interger we label as X-2. What we have done is set up an linear equation to solve this problem. X+(X-1)+(X-2)= -66 mutiplying numbers and X's gives us: 3X-3=-66 Adding three over gives : 3X=-63 Dividing by 3 gives : X=-21 Is this the answer? To find out, plug the X value into the original equation. -21+(-21-1)+(-21-2)= -66  intergers are -21,-22, -23 Ben

Benajmin001 June 01, 2011

Melanie -Simply divide -66 by 3 and this will always get you the middle number of 3 consecutive numbers.-66/3 = -22 = middle number.Since they are consecutive, the other two numbers have to be -21 and -23Hope that helps

Steve204 June 01, 2011